"Chaos rules" revisited - David Murphy (Athabasca University Press, 2011)
About 20 years ago, lost in the midst of my PhD research, I mused over proposed titles. I was pretty pleased with myself to come up with ‘Chaos Rules’ (the implied double meaning was deliberate) or, more completely, Chaos Rules: An Exploration of The Work of Instructional Designers in Distance Education. I used the then emerging theories of chaos and complexity to underpin my analysis. So it was with not just a little excitement that I read the call for contributions to this Special Issue. What follows is a ‘walk through’ my thesis, with an emphasis on the contribution of chaos and complexity theory.